2021
DOI: 10.1111/1365-2435.13794
|View full text |Cite
|
Sign up to set email alerts
|

Leaf silicification provides herbivore defence regardless of the extensive impacts of water stress

Abstract: Altered precipitation patterns due to climate change are likely to impose water‐deficit stress in plants resulting in changes to specific leaf mass, leaf water content and chemical defences that may impact herbivorous arthropods. Grasses, in particular, accumulate large concentrations of silicon (Si) which provides physical defence against herbivores. Although Si uptake by plants may be affected by water availability, very few studies have investigated the combined effect of water‐deficit stress and Si on inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…This may explain why we did not observe further declines in herbivore RGR with endophyte-induced increases in Si concentrations. Furthermore, utilising the same tall fescue cultivar (without endophytes), it has been recently demonstrated that reduced H. armigera RGR in Si-supplemented conditions was associated with the presence of Si-filled silica cells on the leaf surface (Vandegeer et al, 2021). These Si-filled silica cells and other structures (i.e.…”
Section: Si Defences Are Dominantmentioning
confidence: 99%
“…This may explain why we did not observe further declines in herbivore RGR with endophyte-induced increases in Si concentrations. Furthermore, utilising the same tall fescue cultivar (without endophytes), it has been recently demonstrated that reduced H. armigera RGR in Si-supplemented conditions was associated with the presence of Si-filled silica cells on the leaf surface (Vandegeer et al, 2021). These Si-filled silica cells and other structures (i.e.…”
Section: Si Defences Are Dominantmentioning
confidence: 99%
“…During their growth and development, plants are subjected to various environmental stresses. Si has been widely reported to enhance plant tolerance to various abiotic and biotic stresses, such as drought, salt, freezing, nutrient imbalance, radiation damage, metal toxicity, pests, and pathogens 5 , 21 26 . Drought, a recurring phenomenon with major impacts on both humans and natural ecosystems, is the most widespread climatic extreme that hinders primarily crop growth and productivity 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Gutbrodt et al, 2011; Huberty & Denno, 2004), yet results are conflicting, as increased and decreased feeding preferences were observed under drought (Gutbrodt et al, 2011; Huberty & Denno, 2004). Furthermore, the role of Si as well as waterlogging and flooding has been hardly considered in this context (but see Vandegeer et al, 2021). Our data suggest that, for forbs, highly species‐specific effects of Si on herbivory damage across water regimes, including waterlogging and flooding, are likely.…”
Section: Discussionmentioning
confidence: 99%
“…&Denno, 2004). Furthermore, the role of Si as well as waterlogging and flooding has been hardly considered in this context (but seeVandegeer et al, 2021). Our data suggest that, for forbs, highly species-specific effects of Si on herbivory damage across water regimes, including waterlogging and flooding, are likely.…”
mentioning
confidence: 86%